Interactive Learning Multimedia Based on Problem-Based Learning Models in Fifth-Grade Science Content - Arisa Putri Saubari; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2023)
The lack of creative and interactive learning media impacts students' low learning outcomes. This study aims to develop interactive learning multimedia based on problem-based learning models in science content class V. This research belongs to the type of development research with the ADDIE model. The subjects of this study were one subject matter expert, one instructional design expert, one instructional media expert, three students for the individual test, and nine students for the small group test. The data collection method is the questionnaire/questionnaire method and the test method. The instrument used to collect data is a questionnaire. The data analysis techniques are quantitative descriptive and inferential statistical analyses (t-test). The results of the media product validity test showed that the subject matter expert test obtained a presentation of 98.6% (very good). Learning design expert is 92% (very good). Learning media expert is 95% (very good). Individual trials obtained a percentage of 91.3% (very good), and small group trials 90% (very good). In addition, problem-based learning-based interactive multimedia learning on science content shows an effect of problem-based learning-based interactive multimedia on student learning outcomes. It was concluded that multimedia could significantly increase the learning outcomes of fifth-grade elementary school students.